2013
DOI: 10.3892/or.2013.2369
|View full text |Cite|
|
Sign up to set email alerts
|

Embelin-induced brain glioma cell apoptosis and cell cycle arrest via the mitochondrial pathway

Abstract: Abstract. Brain glioma is the most common malignant intracranial tumor and has become the focus of research on diseases of the central nervous system due to its high incidence and poor prognosis. As a small-molecule inhibitor of X-linked inhibitor of apoptosis protein (XIAP), embelin has the ability to specifically inhibit XIAP to control and regulate the apoptosis of various types of tumor cells. However, to date, the mechanism of action for this effect is not well understood. The aim of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In another study, Feresin et al [ 21 ] determined higher MICs against both methicillin-sensitive and methicillin-resistant S. aureus strains at 62 and 250 μ g/mL, which can be explained by different strains used. However, embelin has been previously described for its synergistic antiproliferation interactions [ 22 24 ], but, according to our knowledge, this is the first report of its antimicrobial combinatory activity.…”
Section: Resultsmentioning
confidence: 97%
“…In another study, Feresin et al [ 21 ] determined higher MICs against both methicillin-sensitive and methicillin-resistant S. aureus strains at 62 and 250 μ g/mL, which can be explained by different strains used. However, embelin has been previously described for its synergistic antiproliferation interactions [ 22 24 ], but, according to our knowledge, this is the first report of its antimicrobial combinatory activity.…”
Section: Resultsmentioning
confidence: 97%
“…In the present study, embelin treatment significantly suppressed cell proliferation, induced caspase-3 activation, and increased cell and nuclear apoptosis in the SGC7901 cells. Marsh et al (16) suggested that embelin suppresses the growth of pancreatic cancer in A549 non-small cell lung cancer (17) and brain glioma cells (18). Embelin is considered to be a potential drug for the treatment of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In brain glioma cells, embelin induced apoptosis and G0/G1-phase cell-cycle arrest. In addition, it modulated the shifting of Bcl-2 and Bax to prompt the mitochondrial release of cytochrome c, thereby activating the caspase proteins to induce apoptosis [ 59 ]. Furthermore, embelin induced the expression and oligomerization of voltage-dependent anion channel 1, situated in the outer mitochondrial membrane, which can function as a significant part of the permeability-transition pore that could promote cytochrome c as well as apoptosis-inducing factor release [ 60 ].…”
Section: Apoptosis-pathway Induction By Embelin In Cancermentioning
confidence: 99%